2021
DOI: 10.1186/s12889-021-11166-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses to Covid-19 health certification: a rapid review

Abstract: Background Covid-status certification – certificates for those who test negative for the SARS-CoV-2 virus, test positive for antibodies, or who have been vaccinated against SARS-CoV-2 – has been proposed to enable safer access to a range of activities. Realising these benefits will depend in part upon the behavioural and social impacts of certification. The aim of this rapid review was to describe public attitudes towards certification, and its possible impact on uptake of testing and vaccinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 52 publications
(72 reference statements)
4
40
2
1
Order By: Relevance
“…The findings partially confirm previous research on the public attitude to immunity certificates in the US, UK, and Japan [ 9 , 13 ]. For example, income and personal benefit perception were constantly correlated with attitude to VP, but as a whole, demographic variables that were significantly associated with attitude to VP in the UK, Germany, and Japan, such as gender, age, and education [ 9 ], were not significant predictors of such attitude in the Chinese context.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings partially confirm previous research on the public attitude to immunity certificates in the US, UK, and Japan [ 9 , 13 ]. For example, income and personal benefit perception were constantly correlated with attitude to VP, but as a whole, demographic variables that were significantly associated with attitude to VP in the UK, Germany, and Japan, such as gender, age, and education [ 9 ], were not significant predictors of such attitude in the Chinese context.…”
Section: Discussionsupporting
confidence: 89%
“…For VP, existing studies found a moderate to high public support across countries, with people in the UK and the United States having the most favorite attitude, particularly for international travel [ 10 , 13 , 14 ]. Although varying across contexts, men and older populations generally support the passport [ 9 , 15 ], so do more educated and wealthy people [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the psychological element should not be overlooked. Since it is not possible to completely eliminate the risk of contagion, the mere possession of the COVID Digital Certificate could generate a false sense of security, leading to reckless behaviors that could endanger the health of the individual and of those with whom he or she comes into contact [50]. Another risk worth considering is the abrupt failure of computer systems, either as a result of a virus or cybercrimes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding societal support for the idea of easing restrictions for the immunized population, the empirical evidence is still limited [ 9 ]. However, public and scientific opinion seems to be far from a consensus [ 8 , 18 ].…”
Section: Evidencementioning
confidence: 99%
“…During this transitional phase and due to the perceived safety of vaccination many governments are considering to or are already easing the restrictions for vaccinated as well as for recovered individuals [ 8 , 9 ] – often introducing immunity certificates for this purpose [ 10 ]. Justifications for facilitating vaccinated and recovered individuals are often based on the principle of proportionality of policy measures [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%